War and associative duties - Lazar, S (2009)
Combatants in war inflict untold devastation. They lay waste the environment, destroy cultural heritage, wound, maim, and kill. Most importantly, they kill. These deeds would be, in any other context, paradigmatically unjust. This thesis asks whether they can be justi-fied. There are two possible approaches: first, deny that killing in war is in fact unjust; sec-ond, argue that the injustice is overridden by weightier moral reasons. In Part I, I reject the view that principles of self-defence can render killing in war just. I argue that the most plausible theories of self-defence are hardest to apply in the cha-otic context of war, while the most practicable theories are least philosophically defensible. Moreover, none of them encompasses the inevitable noncombatant deaths that all wars bring. If killing in war is almost always unjust, perhaps we should advocate pacifism. In Part II, I propose an alternative, arguing that these injustices might be all things con-sidered justified. Combatants have morally important relationships: they have deep personal relationships with friends and family, and comrades-in-arms; if they are citizens of just communities, then that relationship is valuable too. I argue that they have associative duties to protect these relationships against the threat posed by war, and that these duties may override the injustices they must commit to avert that threat. After defending a conception of associative duties, I support this conclusion with the following argument. As well as our general duties not to harm, we have general duties to protect. Our general duties to protect sometimes override our general duties not to harm, in particular, in cases of justified humanitarian intervention. Our associative duties to protect, however, are stronger than our general duties to protect. If our associative duties to protect are stronger than our general duties to protect, and our general duties to protect can override our general duties not to harm, then our associative duties to protect should also be able to override our general duties not to harm.